Shaping Bildung durch Wissenschaft: in spite of, contra, and with Bologna (KULT_online, 2021)
In Bildung durch Wissenschaft: Vom Nutzen forschenden Lernens, Jürgen Schlaeger and Heinz-Elmar Tenorth discuss whether the classical formula of “Bildung durch Wissenschaft” (“education through the pursuit of knowledge”) is still central to the German university, which is now characterised by substantial changes through Bologna and national reforms. The authors, themselves long-term university observers, practicians, and reformers, further discuss how “Bildung durch Wissenschaft” can be imparted to students nowadays.